ACTIVE ANTENNA FOR GPS/GLONASS/EGNOS SATELLITE SYSTEMS SIGNALS RECEIVING - I. Yu. Malevich; Y. Y. Bobkov; E. N. Kalenkovich; M. I. Kruchkov; A. S. Lopatchenko (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The article describes the result of development and laboratory testing of the active antenna for receiving signals of satellite systems GPS/GLONASS/EGNOS with powered from the RF cable. The antenna element is designed on a ceramic substrate with high permittivity and reduced dimensions.